Heat bonding of wood with starch-lignin mixtures creates new recycling opportunities. (November 2022) - Hellmayr, R.; Šernek, M.; Myna, R.; Reichenbach, S.; Kromoser, B.; Liebner, F.; Wimmer, R.
Abstract: Engineered wood products are a meaningful approach to overcome some limitations inherent to wood, such as inhomogeneity and dimensional constraints. Wood adhesives play a key role in this concept; however, their bonding chemistry hitherto impedes facile separation of the components at the end of the service life of engineered wood products. Besides lacking recyclability, environmental safety and sustainability are further issues that could be improved. Herein, we present an inexpensive bio-adhesive system that could pave way towards a novel generation of sustainable engineered wood products. Following a four-stage experimental design to assess the impact of various process parameters, it has been shown that aqueous mixtures of equal quantities of corn starch and sodium lignosulfonate (BIOMIX) feature excellent bond characteristics when subjected to hot pressing (150°C, 0.2 MPa, 60 s), comparable with that of commercial urea-formaldehyde (UF) adhesives. Activation of starch beforehand by gelatinization is not required as granule opening, chain disentanglement and plasticization occur during pressing as confirmed by polarized light microscopy and differential scanning calorimetry (DSC). The presence of sodium lignosulfonate is essential due to its water retarding, dispersing and plasticizing abilities. Preliminary recyclability tests of beech veneer assemblies glued with BIOMIX revealed that facile hydrolysis of the glueline (60 min) and subsequent re-bonding without the addition of new adhesive reaches almost the initial shear strength values as investigated using an automated bonding evaluation system (ABES).